2008
DOI: 10.1097/olq.0b013e318164e567
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Human Papillomavirus Genotypes Among High-Risk Women: A Comparison of Hybrid Capture and Linear Array Tests

Abstract: Performance of HCII and LA does not significantly differ in detecting CIN2+ or CIN3+.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
23
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 38 publications
5
23
1
1
Order By: Relevance
“…Specifically, 8 of 15 specimens that were HR HPV negative and LR HPV positive by hc2 were subsequently found to have HR genotypes by LA. This is not surprising, as previous studies comparing hc2 and LA have reported a slightly higher sensitivity, but lower specificity, with the LA (11,14,20,28).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Specifically, 8 of 15 specimens that were HR HPV negative and LR HPV positive by hc2 were subsequently found to have HR genotypes by LA. This is not surprising, as previous studies comparing hc2 and LA have reported a slightly higher sensitivity, but lower specificity, with the LA (11,14,20,28).…”
Section: Discussionmentioning
confidence: 56%
“…The LA has previously demonstrated sensitivity comparable to that of the hc2 (11,14,20,28) and was used in this study to resolve discordant hc2 and c4800 results and confirm paired-positive results. Total nucleic acid was extracted from 400 l of LBC specimen and eluted into 110 l using the easyMAG extractor (bioMérieux Canada Inc., Québec, Canada).…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…HPV DNA detection and genotyping were carried out using the Linear Array (LA) HPV Genotyping Test (Roche Diagnostics). Briefly, HPV DNA was amplified by PCR using a pool of biotin-labeled primers that hybridize in the L1 region (18,23,24 (25). For the purposes of this study, undetermined-risk and LR HPV types were combined.…”
Section: Methodsmentioning
confidence: 99%
“…2) with several signs of inflammatory activation in the cervical biopsy. However, the test was negative for HPV DNA at inclusion as well as at follow-up, and the sensitivity of Linear Array is very high (44,45). None of the women had a clinically overt lesion; thus, we may not have taken the biopsy at the site of infection/inflammation.…”
Section: Discussionmentioning
confidence: 99%